MICROFOCUSED ULTRASOUND FOR BICHECTOMY EFFECT - Vieira Melo Aguiar, Saskya; Regina Veronezi, Lauscea; Vivianne Nogueira, Marcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
The search for aesthetic treatments is becoming increasingly common in clinics, with facial slimming being one of the most sought-after procedures. In an effort to address techniques less invasive than surgical procedures, the use of Microfocused Ultrasound (MFU) has been gaining prominence. This case report aims to evaluate the efficacy of MFU in facial slimming for a patient seeking to improve the contour of her face. Methodology: The treatment area was delimited by a line drawn from the labial commissure to the tragus, with a safety margin of 1cm on both sides. Both areas were divided into three columns (anterior, middle, and posterior) to receive the transducers. Ultrasound gel was applied to the skin before the procedure. The technology used was Reface. Initially, 4 MHz transducers with 4.5 mm depth and 0.9J power were applied to the area with 15 shots on both sides of the face, distributed as follows: six in the anterior column, six in the middle column, and three in the posterior column. Next, a 7 MHz transducer with 3.0 mm depth and 0.9J power was applied to the area with 15 shots on each side of the face, distributed similarly. The transducers were reoriented with each shot, advancing 1mm upward in both areas. These areas were chosen with the goal of slimming the middle third of the face. Results: The patient was evaluated after 60 days, and a reduction in volume on the left and right sides of the face, ranging from 1.02 to 1.79mm, was observed. The results were obtained through standardized photographs using Vectra software.